Pengaruh Saham Dan Reksadana Syariah Terhadap Pertumbuhan Ekonomi Indonesia Tahun 2013-2019 - Nur Auliyatusaa'adah; Dwi Irma Handayani; farekha farekha (Departement of Sharia Economics, Faculty of Islamic Economics and Business, Universitas Islam Negeri K.H Abdurrahman Wahid Pekalongan, 2021)
The purpose of this study is to determine partially and simultaneously between Islamic stocks and Islamic mutual funds on economic growth. The population in this study is Islamic stocks and Islamic mutual funds in the Financial Services Authority data and the value of Indonesia's GDP at the Central Statistics Agency. While the sample is quarterly report data on Islamic stocks with indicators of ISSI, Islamic mutual funds and economic growth through the value of GDP in the Central Statistics Agency data for 7 years from 2013 to 2019. Data analysis using multiple linear regression analysis. There are several conclusions from this study: (1) Sharia stocks have a significant effect on Indonesia's economic growth in 2013-2019, (2) Islamic mutual funds have a significant effect on Indonesia's growth in 2013-2019, (3) Sharia stocks and Islamic mutual funds together had a significant effect on Indonesia's economic growth in 2013-2019.